Immunopeptides: immunomodulatory strategies and prospects for ocular immunity applications - Tang, Yi; Qu, Sheng; Ning, Zichao; Wu, Hong (Frontiers in Immunology, 2024)
Immunopeptides have low toxicity, low immunogenicity and targeting, and broad application prospects in drug delivery and assembly, which are diverse in application strategies and drug combinations. Immunopeptides are particularly important for regulating ocular immune homeostasis, as the eye is an immune-privileged organ. Immunopeptides have advantages in adaptive immunity and innate immunity, treating eye immune-related diseases by regulating T cells, B cells, immune checkpoints, and cytokines. This article summarizes the application strategies of immunopeptides in innate immunity and adaptive immunity, including autoimmunity, infection, vaccine strategies, and tumors. Furthermore, it focuses on the mechanisms of immunopeptides in mediating ocular immunity (autoimmune diseases, inflammatory storms, and tumors). Moreover, it reviews immunopeptides’ application strategies and the therapeutic potential of immunopeptides in the eye. We expect the immune peptide to get attention in treating eye diseases and to provide a direction for eye disease immune peptide research.